2022
DOI: 10.3390/ijerph191912072
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Low Birthweight and Preterm Birth in Post-Conflict Northern Uganda: A Community-Based Cohort Study

Abstract: Background: Annually, an estimated 20 million (13%) low-birthweight (LBW) and 15 million (11.1%) preterm infants are born worldwide. A paucity of data and reliance on hospital-based studies from low-income countries make it difficult to quantify the true burden of LBW and PB, the leading cause of neonatal and under-five mortality. We aimed to determine the incidence and risk factors for LBW and preterm birth in Lira district of Northern Uganda. Methods: This was a community-based cohort study, nested within a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Another notable finding of the current study was that maternal anemia increased the risk of LBW by 4.7 times. Several studies have also reported similar findings for other regions of Sudan and Africa—Wad Mani in Central Sudan ( Elhassan et al, 2010 ), Kassala in Eastern Sudan ( Ali et al, 2011 ), Darfur in Western Sudan ( Haggaz et al, 2010 ), Ethiopia ( Deriba and Jemal, 2021 ; Tadesse et al, 2023 ), Somalia ( Barut and Mohamud, 2023 ), Sierra Leone ( Kargbo et al, 2021 ), Uganda ( Odongkara et al, 2022 ), and Ghana ( Mohammed et al, 2019 ). This association was further corroborated by several meta-analyses that have shown that anemic pregnant women are at a higher risk of delivering newborns with LBW ( Rahman et al, 2016 ; Young et al, 2019 , 2023 ).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Another notable finding of the current study was that maternal anemia increased the risk of LBW by 4.7 times. Several studies have also reported similar findings for other regions of Sudan and Africa—Wad Mani in Central Sudan ( Elhassan et al, 2010 ), Kassala in Eastern Sudan ( Ali et al, 2011 ), Darfur in Western Sudan ( Haggaz et al, 2010 ), Ethiopia ( Deriba and Jemal, 2021 ; Tadesse et al, 2023 ), Somalia ( Barut and Mohamud, 2023 ), Sierra Leone ( Kargbo et al, 2021 ), Uganda ( Odongkara et al, 2022 ), and Ghana ( Mohammed et al, 2019 ). This association was further corroborated by several meta-analyses that have shown that anemic pregnant women are at a higher risk of delivering newborns with LBW ( Rahman et al, 2016 ; Young et al, 2019 , 2023 ).…”
Section: Discussionsupporting
confidence: 63%
“…Similar to previous studies from Sudan ( Elhassan et al, 2010 ; Haggaz et al, 2010 ), the current study did not report any association between certain maternal factors, such as age, parity, education level, and anthropometrics, and LBW. On the other hand, a maternal age of ≥35 years in Uganda was reportedly associated with LBW ( Odongkara et al, 2022 ). Likewise, parity and LBW were found to be associated in studies from Ghana ( Mohammed et al, 2019 ) and Tanzania ( Kamala et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though many studies have been carried out elsewhere, Little data and literature have been done about preterm birth in Uganda, especially at Lira Regional Referral Hospital therefore, this study will make a significant contribution to assessing the prevalence of preterm birth and its associated factors among mothers delivered at Lira Regional Referral Hospital. Many mothers have had or experienced a preterm birth in their lives which poses a threat to their lives and babies, though the Ministry of Health has tried in its efforts to reduce the prevalence of preterm birth by improving healthcare systems [10], the problem is still evident and on the rise. Globally, 15 million babies are born preterm of which 60% of the cases occur in Africa and Asian countries.…”
Section: Introductionmentioning
confidence: 99%